Optimasi Suhu Laddle Refining Furnace (LRF) pada Pengolahan Baja Karbon Tinggi dengan Menerapkan Metode Fuzzy Mamdani - Cahyaningtias, Sari; Purnaningrum, Evita (Universitas Dr. Soetomo, 2019)
Steel processing in large scale industries has several stage namely melting, moulding, fetling, and finishing. The melting process requires such a right temperature particularly in Refining Ladle Furnace (LRF) that is a main point of the process itself. The optimum time of LRF can minimize both production time and electricity in which avoid steel clumping in the next step. This research aims to find the optimum temperature of high carbon steel in the ladle and to gain the relation between rate of carbon composition in steel with heating time using Mamdani Method. The method is also known as min-max method and consists of four stages: form fuzzy set, apply implication function, composition, and defuzzification. The simulation results optimal temperature of high carbon steel stood at between 15300C-15700C and low carbon 15850C-15950C. It shows that the temperature depends on the carbon composition and each grade of liquid temperature.